Impact of the First SARS-CoV-2 Lockdown on Adherence to Biological Treatment in Patients with Immune-Mediated Inflammatory Diseases in the Netherlands - van der Groef R; de Jong PHP; Hijnen DJ; van der Woude CJ; van Laar JAM; van der Kuy PHM; Brugma JD; Pasma A (Patient Preference and Adherence, 2023)
Romy van der Groef,1 Pascal HP de Jong,1 Dirk Jan Hijnen,2 Christien J van der Woude,3 Jan AM van Laar,4 P Hugo M van der Kuy,5 Jan-Dietert Brugma,6 Annelieke Pasma1 1Department of Rheumatology, Erasmus University Medical Center, Rotterdam, the Netherlands; 2Department of Dermatology, Erasmus University Medical Center, Rotterdam, the Netherlands; 3Department of Gastroenterology and Hepatology, Erasmus University Medical Center, Rotterdam, the Netherlands; 4Department of Internal Medicine and Immunology, Erasmus University Medical Center, Rotterdam, the Netherlands; 5Department of Clinical Pharmacy, Erasmus University Medical Center, Rotterdam, the Netherlands; 6Department of Outpatient Pharmacy, Erasmus University Medical Center, Rotterdam, the NetherlandsCorrespondence: Romy van der Groef, Erasmus University Medical Center, Department of Rheumatology, Room Na-523, PO Box 2040, 3000 CA, Rotterdam, the Netherlands, Tel +31 648284141, Email r.vandergroef@erasmusmc.nlPurpose: During the SARS-CoV-2 pandemic, national and international societies have recommended continuing biological agents in patients with immune-mediated inflammatory diseases (IMID) in the absence of SARS-CoV-2 symptoms. However, adherence to biological treatment might decrease, because these recommendations contradict patients’ beliefs. Especially an increased concern about side effects could have influenced the adherence to biological treatment during the first lockdown. The primary objective was to investigate the impact of the first SARS-CoV-2 lockdown on adherence to biological treatment in IMID patients.Patients and Methods: In this prospective cohort study, IMID patients who received a biological agent before and during the first SARS-CoV-2 lockdown (March 2020- June 2020) were included. Patients were excluded if they did not complete the medication adherence report scale-5 (MARS-5) questionnaire at ≥ 1 visit before the lockdown and ≥ 1 visit during the lockdown. Adherence to biological treatment was measured with the MARS-5 and Medication Possession Ratio (MPR).Results: We included 157 IMID patients. The percentage of adherent patients, defined as MARS-5 score > 21, was significantly lower during the lockdown compared to the period before the lockdown (88.5% vs 84.1%, p< 0.001). Additionally, the overall percentage of adherent patients during the lockdown based on the MPR ≥ 90% was significantly lower compared to adherence based upon the MARS-5 (65.1% vs 84.1%, p< 0.001).Conclusion: This study showed that the first SARS-CoV-2 lockdown negatively impacts adherence to biological treatment in IMID patients. Therefore, treating physicians should be aware of this problem to minimize the potential harmful effects of non-adherence.Keywords: adherence, biological, SARS-CoV-2, immune-mediated inflammatory diseases